Journeying Toward Decolonial Child and Youth Care / Indigenous Child and Youth Care: Weaving Two Heart Stories Together (Cherylanne James, 2023) - Boody, Lois (Journal of Childhood Studies, 2024)
Indigenous Child and Youth Care: Weaving Two Heart Stories Together by Cherylanne James is discussed in this review as a critical contribution to child and youth care education in Canada. James’s Indigenous feminist orientation invites child and youth care students to unlearn colonial narratives, to instead center Indigenous approaches to care. The reviewer highlights the effectiveness of James’s approach in engaging in “difficult knowledge” with learners to foster relational accountability, and shares how this approach models “journeying,” moving from deficit-centered orientations toward Indigenous-led, desire-based approaches for decolonial care. The text guides child and youth care students to reflect critically on their role in supporting Indigenous futurities.